Addressing the consequences of missing vaccines: A case report of pertussis in a child with acute lymphoblastic leukemia - Diana Marcela Perea Rojas; Indiana Luz Rojas Torres; Luis Enrique Perea Vásquez (Respiratory Medicine Case Reports)
Pertussis, caused primarily by Bordetella pertussis and occasionally by Bordetella parapertussis, remains a major public health issue despite widespread vaccination efforts. Immunocompromised children, such as those with acute lymphoblastic leukemia, are particularly susceptible to vaccine-preventable diseases, underscoring the importance of ensuring adequate vaccination coverage. We report a case of a 3-year-old boy with ALL who developed a Bordetella parapertussis infection during chemotherapy. The child's lack of documented pertussis vaccination underscores critical gaps in primary healthcare and immunization practices. His case highlights the increased risk of severe infections in unvaccinated, immunocompromised patients and underscores the necessity of maintaining comprehensive vaccination records and robust primary healthcare systems to prevent such infections. The rapid diagnosis and initiation of appropriate antimicrobial therapy, highlights the critical role of early detection and tailored interventions in preventing severe outcomes.